Characterization of cell lines derived from tumors induced by TC-1 cells in mice preimmunized against HPV16 E7 oncoprotein - Smahel, Michal; Smahelová, Jana; Tejklová, Pavla; Tachezy, Ruth; Marinov, Iuri (International journal of oncology, 2005)
Escape of tumor cells from the host immune system is probably the most difficult obstacle to overcome in attempts to enhance the efficacy of immunotherapy of tumors. To solve the problem, animal models with escape mechanisms found in human tumors are needed. We have already established cell lines with substantially reduced expression of MHC class I molecules that were derived from oncogenic TC-1 cells producing E6 and E7 oncoproteins of HPV16. In this study, we prepared other cell lines from TC-1-induced tumors formed infrequently in mice immunized against the E7 antigen. These clones differed in morphology and both in vitro and in vivo growth properties. After vaccination with the highly efficient anti-E7 DNA vaccine several clones appeared to be quite resistant to induced anti-tumor immunity. Detection of the production of the MHC class I molecules and B7.1 costimulatory molecule did not provide clues to understand the mechanism of immunoresistance of the clones. Therefore, we performed transcriptional profiling using Atlas Mouse Cancer 1.2 Array (BD Clontech). Among the genes differently expressed in the examined cell lines were those of three cytokines influencing immune cells: MCP-1, osteopontin, and midkine. Altered secretion of MCP-1 chemokine was verified by ELISA. In addition, expression of the E7 oncogene was reduced in all TC-1 clones. Most importantly, one of anchor amino acids in the immunodominant epitope of E7 was mutated in all immunoresistant clones. Such mutations of HPV oncogenes must be considered in therapeutic-vaccine development and evaluation.
Keywords: genetická transkripce; sekvence nukleotidů; buněčné klony; messenger RNA; B7-1 Antigen; tvar buňky; Histocompatibility Antigens Class I; Oligonucleotide Array Sequence Analysis; Neoplasms, Experimental; Transcription, Genetic; antigeny CD80; onkogenní proteiny virové; Female; mutace; polymerázová řetězová reakce s reverzní transkripcí; Reverse Transcriptase Polymerase Chain Reaction; zvířata; proliferace buněk; myši; Oncogene Proteins, Viral; myši inbrední C57BL; chemokin CCL2; Mice; buněčné linie; Amino Acid Sequence; RNA, Messenger; Papillomavirus E7 - proteiny; Neoplasm Metastasis; metastázy nádorů; Clone Cells; ženské pohlaví; Cell Line; experimentální nádory; Base Sequence; Chemokine CCL2; Cell Shape; Cell Proliferation; stanovení celkové genové exprese; Mice, Inbred C57BL; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; nádorové buněčné linie; Animals; Cell Line, Tumor; Gene Expression Profiling; Mutation; MHC antigeny I. třídy; Papillomavirus E7 Proteins; sekvence aminokyselin